Analiza elementów tworzących stopę wzrostu wartości udziałów w metodzie wyceny mnożnikiem cena/zysk - Słoński, Tomasz (The Components of Stock Price Growth Rate in Discounted Dividend Model and P/E Valuation, 2007)
The P/E valuation method incorporates specific assumptions concerning the stock price growth. In the base case, the set of assumptions which holds in the Discounted Dividend Model was introduced. This set of assumptions allows to obtain proper results only if the company experiences the stable growth of its revenues and earnings. The precise interpretation of stock price growth includes an additional parameter, i.e. an expected change of P/E ratio. A more detailed interpretation was used to describe possible stock price movements for Prokom SA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 498-506